Fluorescência da clorofila a como indicador de porta enxertos de manga ‘Ubá’ mais tolerantes ao déficit hídrico - Silva, Leonardo Faria (2020)
In order to select the photochemical parameters extracted from the chlorophyll a fluorescence kinetics as being the simplest, fastest and most efficient for early identification of the most vigorous rootstock in the formation of drought tolerant 'Ubá' see